Performance of ultrasonic – Treated nano-zeolites employed in the preparation of dimethyl ether - Sanaa M. Solyman; Noha A.K. Aboul-Gheit; Fathia M. Tawfik; M. Sadek; Hanan A. Ahmed (Egyptian Journal of Petroleum)
Catalytic dehydration of methanol to dimethyl ether was carried out over nano-zeolites and their modified samples via ultrasonic technique. Parent H-Beta and Parent H-Mordenite zeolites are used as synthesized and after sonication. H-Mordenite sonicated for 20 and 120 min whereas H-Beta sonicated for 20 min only. The reaction temperature was varied between 100 and 225 °C at three different contact times. The different catalyst samples were characterized using: XRD, FTIR, TEM, SEM and NH3-TPD techniques. The results revealed that sonication of parent zeolite samples affects on the unit cell dimensions and their crystal size. FTIR-spectroscopic analysis indicated that sonication may decrease the pore opening and cause framework structure defects. TEM and SEM micrographs showed that sonication broke-up and re-ordered zeolite crystals with longer time resulted in a different morphology relative to parents and also change the particle size. Sonicated samples have a good performance in methanol dehydration with complete conversion and complete selectivity to dimethyl ether at lower temperature relative to the corresponding parent zeolites. TPD results indicated that the concentration of strong acid sites decreased in sonicated H-Mordenite samples leading to an increase of their catalytic activity and the selectivity to DME. On the other hand, ultrasonic treatment of H-Beta sample decreased its catalytic activity.